Tele-accelerometry as a novel technique for assessing functional status in patients with heart failure: Feasibility, reliability and patient safety - Jehn, Melissa; Prescher, Sandra; Koehler, Kerstin; Von Haehling, Stephan; Winkler, Sebastian; Deckwart, Oliver; Honold, Marcus; Sechtem, Udo; Baumann, Gert; Halle, Martin; Anker, Stefan D.; Koehler, Friedrich (International Journal of Cardiology, 2013)
Background The six-minute walk test (6MWT) is an established measure of functional exercise capacity associated with clinical prognosis in Chronic Heart Failure (CHF). The aim of this study is to evaluate the employment of tele-accelerometry for the remote assessment of 6MWT in CHF. Methods 155 patients were subjected to tele-accelerometry in form of monthly 6MWTs in their home surroundings. Accelerometer output included steps/6 min and walking speed. Data was directly transferred via mobile network to the Telemedicine Centre subsequent to test completion. 6MWT distance was measured by hand wheel and steps were counted with a digital hand-counter at baseline (Test 1) and at 12 months follow-up (Test 2). Results Accelerometer accuracy was within the 99th percentile. There was a significant correlation between step count, walking speed and measured 6MWT distance (Test 1: steps: r = 0.80, P < 0.001; Test 2: steps: r = 0.90, P < 0.001 and Walking Speed Test 1: r = 0.80, P < 0.001; Walking Speed Test 2: r = 0.86, P < 0.001). The reproducibility of tele-accelerometry was within 95% margin for all performance parameters, which showed stronger associations to quality of life questionnaire (Short Form - 36) Physical Component Score (PCS) than New York Heart Association (NYHA) functional class. Conclusion Tele-accelerometry is feasible in patients with CHF and output parameters are indicative of exercise capacity. The benefit of this approach lies in its simplicity under every day circumstances by enabling routine performance testing to assess patients' functional status. © 2013 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 6-Minute walk test; Activity monitoring; Exercise testing; Systolic heart failure; Telemedicine; TIM-HF trial